PENGARUH PENGALAMAN KERJA, AKUNTABILITAS DAN BESARAN FEE AUDIT TERHADAP KUALITAS AUDIT PADA KAP DI INDONESIA TAHUN 2021 - Dewi Oktaviyani; Leonard Pangaribuan (Jurnal Akuntansi, 2021)
A public accountant (auditor) who has a lot of experience, has an attitude towards what is reported or is reported to be responsible in the company's financial statements is very necessary at this time. That way, an auditor who has a high attitude of responsibility will be trusted to provide good audit quality. The data obtained in this study came from a questionnaire filled out by 50 respondents who are auditors or public accountants (auditors) registered at the Indonesian Institute of Certified Public Accountants. The results show that the variability of audit quality that can be explained by work experience, accountability and the amount of audit fees is only 35%. The results of the statistical test value stated that if work experience had a significance of 0.1825 (>0.05), accountability had a significance value of 0.007 (0.05). The result is that work experience, accountability and the amount of audit fees together have an effect on audit quality. Partially, only accountability has a positive effect on audit quality, while work experience and the amount of audit fees have no effect on audit quality.